The Impact of COVID-19 on Domestic Travel: The Spatial Changes in Taiwan - Kiss, Robert; Patev, Plamen; Lan, Kou-Wei (Modern Geográfia)
This paper aims to provide an overview of Taiwanese domestic tourism’s spatial changes during the pandemic era. The research examines five years of domestic tourism flow in Taiwan. Based on the Taiwan Centers for Disease Control’s (CDC) regular reports, we analyzed 744 data categories grouped into eight clusters: international epidemic, major events, border policy, material preparation, community epidemic prevention, relief/compensation policy, inspection/R&D policy, and medical facility control. We defined six pandemic periods based on these factors to analyze the domestic tourism landscape during these eras. A comparative analysis of monthly travel data from local governments and tourism administrations across various periods was conducted. For analysis, we used Tableau, while Corel Draw was applied to map the spatial distribution of domestic travel. By categorizing Taiwan’s geographical areas based on their landscape characteristics and tourism images, we analyzed their domestic tourism performance during this five-year timeframe. The major finding was that domestic tourism significantly benefited from the lockdown situation, generating increased domestic travel and higher industry revenues. The “Bubble period,” when effective local health policies enabled safe travel, was particularly successful. Additionally, the post-COVID period’s domestic travel and revenues surpassed those of the pre-pandemic era.